Acrylamide mitigation in bakery products - Jesus, Susana (2017)
The aim of this study was the determination of acrylamide in Portuguese bakery and its reduction in a bakery product. Acrylamide is considered by the International Agency for Research on Cancer as a carcinogenic compound to animals and probably to humans. For this study a total of 30 samples of god bread, “trouxa filó”, pies, ham and cheese rollings, muffins, pastels, and cookies were randomly collected in several commercial establishments. Sample preparation involved solid phase extraction and for the quantification of acrylamide a ultra-performance liquid chromatography-tandem mass spectrometer (UPLC-MS/MS) was used. The ham and cheese rolling and “trouxa filó” had the highest amount of acrylamide, 3743 µg/kg, and 3862 µg/kg, respectively. The results also showed that caramel cookies, butter cookies, Greek cookies and cocoa cookies do not exceed the EFSA indicative value (500 μg/kg) (EFSA, 2015). Pie samples(686-1084 μg/kg), god's bread(995 μg/kg), pastels(527-809 μg/kg) and muffins(676-1057μg/kg) contain high levels of acrylamide when compared to the values found in the literature for bakery products, 198 μg/kg (Mojska, Gielecińska, Szponar, & Ołtarzewski, 2010). Given the obtained results, tests were carried out in order to reduce the concentration of acrylamide. A bakery product was prepared to which four different reducing agents (A, B, C and D) were individually added. The effect of each agent on acrylamide formation was evaluated. Results showed that mixture B obtained an acrylamide reduction of 5.6%. On the other hand, the remaining mixtures increased the production of the contaminant. Yet, it was found that the decrease obtained with mixture B is still not sufficient since it remains above the indicative value of EFSA. Thus, further studies are necessary in order to achieve a higher percentage of reduction of acrylamide. Progress studies are ongoing with other reducing agents and flours.